Phenology of Vegetation of Pulwama (Kashmir, India) - Navchoo, Irshad A.; Kachroo, P. (Indian Forester, 1986)
In this paper broad phenological aspects of vegetation of Pulwama are reported. The studies reveal that the vegetation of Pulwama is in general seasonal and governed by the environmental factors. The life span of the plants are broadly classified as short-term and longterm plants.